2014
DOI: 10.1371/journal.pone.0087381
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Genetic Diversity and Complex Population Structure of Siberian Apricot (Prunus sibirica L.) in China as Revealed by Nuclear SSR Markers

Abstract: Siberian apricot (Prunus sibirica L.), an ecologically and economically important tree species with a high degree of tolerance to a variety of extreme environmental conditions, is widely distributed across the mountains of northeastern and northern China, eastern and southeastern regions of Mongolia, Eastern Siberia, and the Maritime Territory of Russia. However, few studies have examined the genetic diversity and population structure of this species. Using 31 nuclear microsatellites, we investigated the level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
51
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 56 publications
11
51
1
Order By: Relevance
“…Fewer heterozygotes were observed at the population level, except in G population. Similar findings have been reported in many other tree species (Veron et al, 2005;Hadziabdic et al, 2012;Wang et al, 2014). A process of inbreeding in these trees, such as partial selfing (Veron et al, 2005), effect of biparental breeding because of limited pollen dispersal among relatives (Hadziabdic et al, 2012), and the result of half-sibling mating occurring over a small geographical area, may have caused the heterozygote deficiency .…”
Section: Discussionsupporting
confidence: 77%
“…Fewer heterozygotes were observed at the population level, except in G population. Similar findings have been reported in many other tree species (Veron et al, 2005;Hadziabdic et al, 2012;Wang et al, 2014). A process of inbreeding in these trees, such as partial selfing (Veron et al, 2005), effect of biparental breeding because of limited pollen dispersal among relatives (Hadziabdic et al, 2012), and the result of half-sibling mating occurring over a small geographical area, may have caused the heterozygote deficiency .…”
Section: Discussionsupporting
confidence: 77%
“…; Wang et al . ). Further research on the Chinese cultivated and wild apricot(s), together with representatives of closely related species ( P. siberica, P. mandshurica, P. mume and P. ansu ), is required to infer the precise diversity and population structure of apricot in China.…”
Section: Discussionmentioning
confidence: 97%
“…Siberian apricots in China were divided into two subpopulations (Li et al, 2014) and into four subpopulations in another study (Wang et al, 2014), and molecular findings have shown that no significant difference is detected between the wild and semiwild groups, indicating that recent cultivation practices have had little impact on the genetic diversity of Siberian apricots (Wang et al, 2014). The common apricots of Mediterranean countries were studied by Bourguiba et al (2012), and 207 accessions were subdivided into three main gene pools when K = 3: Irano-Caucasian, North Mediterranean Basin and South Mediterranean Basin.…”
Section: Discussionmentioning
confidence: 99%